2020
DOI: 10.1080/14767058.2020.1791817
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on COVID-19 pregnancy: a cases series during outbreak in Bergamo Province, North Italy

Abstract: Background: COVID-19 has rapidly spread worldwide, with severe complications affecting particularly elderly and compromised subjects. Less information about COVID-19 in pregnancy has been reported so far in the literature. Methods: Case series on pregnancies complicated by COVID-19. All cases were diagnosed at Bolognini Hospital, Seriate, Italy. These cases are presented to clarify the features of COVID-19 occurring in pregnancy. Results: Four women had symptoms of COVID-19 during pregnancy or immediately afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 14 publications
0
24
0
2
Order By: Relevance
“…In total, the studies reported findings from 325 women whose pregnancy outcome was known following SARS-CoV-2 infection, seven of which were twin pregnancies [ 25 , [31] , [32] , [33] , [34] , [35] ], six pregnancies were terminated (one for maternal health reasons [ 18 ], one for personal reasons [ 19 ], three for “personal choice” [ 21 ] and one where the reason was unclear [ 17 ]). Of the remaining pregnancies, 83 births (58%) were by Caesarean section and no information was provided in 16 cases.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, the studies reported findings from 325 women whose pregnancy outcome was known following SARS-CoV-2 infection, seven of which were twin pregnancies [ 25 , [31] , [32] , [33] , [34] , [35] ], six pregnancies were terminated (one for maternal health reasons [ 18 ], one for personal reasons [ 19 ], three for “personal choice” [ 21 ] and one where the reason was unclear [ 17 ]). Of the remaining pregnancies, 83 births (58%) were by Caesarean section and no information was provided in 16 cases.…”
Section: Resultsmentioning
confidence: 99%
“…# cases only included if specified as spontaneous preterm birth. Maternal Medical Condition Number of women Percentage of total cases examined (%) References Gestational diabetes 7 2 [ 19 , 20 , 28 , 33 , 60 ] Pre-existing diabetes 2 0.6 [ 21 , 57 ] Hypertensive disorders of pregnancy 18 5 [ 18 , 19 , 21 , 24 , 25 , 28 , 31 , 53 , 60 ] Obstetric cholestasis 1 0.3 [ 28 ] Acute cholecystitis 1 0.3 [ 52 ] Cardiovascular disease 1 0.3 [ 21 ] Metabolic acidosis 1 0.3 [ 51 ] Respiratory failure 2 0.6 [ 24 , 25 ] Preterm prelabour rupture of membrane …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations